Selected trace element uptake by rice grain as affected by soil arsenic, water management and cultivar -a field investigation - Farrow, Eric M.; Wang, Jianmin; Shi, Honglan; Yang, John; Hua, Bin; Deng, Baolin (Frontiers in Environmental Science, 2024)
Accumulation of arsenic (As) in rice grain was reported in many regions of the world, including the United States, which has been a threat to human health. This field research investigated the grain As accumulation and its relationship with the uptake of selenium (Se), molybdenum (Mo), and cadmium (Cd) in the monosodium methanearsonate (MSMA) amended soil, as affected by selected rice cultivars and water management. Results indicated that MSMA increased the accumulation of As and Se but decreased Mo for all six cultivars under four irrigation management. MSMA also increased grain-Cd in some cultivars. In no As-amended soil, intermittent flooding decreased grain-As by 66%, grain-Se by 21%, and grain-Mo by 63%, but increased grain-Cd by 64% in Zhe 733, a straighthead resistant cultivar, while in MSMA-amended soil, intermittent flooding decreased grain-As by 63% and grain-Mo by 44% but increased grain-Se by 68% and grain-Cd by three times. For all other five cultivars, intermittent flooding generally decreased grain-As and grain-Mo but increased grain-Se and grain-Cd. Zhe 733 cultivar resulted in the lowest grain concentrations of all trace elements in all water treatments. A negative As-Se correlation and a positive grain As-Mo correlation were significant but not the As-Cd correlation. This research showed that the uptake of As, Se, Mo, and Cd by rice grain occurred as a complex function of multiple variables, including cultivar type and soil chemistry. As a result, accumulation of As and trace elements in rice grain may be controlled by selecting appropriate cultivars and water management practices.